DESKRIPSI MANAJEMEN LABORATORIUM KIMIA DI SMA NEGERI 8 DAN SMA MUHAMMADIYAH 1 PONTIANAK - Trisanty, Yulia; Masriani, Masriani; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLaboratory management comprehension in school was very important for headmaster, the chemical teacher, and laboratory staff. This study aims was to describe chemical laboratory management SMA Negeri 8 and SMA Muhammadiyah 1 Pontianak. The method of the research was using descriptive research with technique of collecting data were direct observation, indirect observation, and documentation technique. The data collection tool was using observation, questionnaire, and documentation.  The result of this research showed that the management of the chemistry laboratory from planning, organizing, implementating, and controlling get into the category very well based on Guttman scale. The chemistry laboratory in both  schools have not reached minimum standard of chemistry laboratory equipment. Keywords: laboratory management, planning, organizing, implementating, controlling